Collaborations on blood transfusion research in sub‐Saharan Africa: who, what and where. Issue 3 (5th February 2020) - Fisher, Amelia; Wallis, Selina; Hassall, Oliver; Martin, Russell; Bates, Imelda
Abstract : Background and objectives: Children and pregnant women use 75% of the blood supply in sub‐Saharan Africa (SSA) but face widespread blood shortages. To increase safe blood supply, Africa‐specific evidence and strengthened capacity for transfusion research are needed. Our study analysed seven years of SSA transfusion publications, compared researched topics against priorities and enumerated SSA transfusion research collaborations. Materials and methods: Data on research topic, journal type, authors' institutions and country were extracted from transfusion‐related SSA articles published between 2008 and 14 and used to construct a quantitative, graphic visualization of collaborations. Research topics were compared to those identified as priorities for SSA blood services in 2008 and 2015. Results: Of the 2176, 267 articles (average 38/year) met criteria for analysis. They involved 1245 authors, 673 institutions, 59 countries (35 SSA) and 1375 collaborations. About 41% were on transfusion‐transmitted infections. About 34% were published in specialist transfusion journals. Only 7% involved exclusively collaborations within SSA. Two of the top fifteen institutions by publication quantity were from outside SSA. Conclusion: Despite a general paucity of SSA‐relevant transfusion research, Francophone SSA was well‐represented. Published research topics are not well matched to SSA research priorities; research on supply, distribution, financing and systems is particularly neglected. The study provides a baseline against which to track any refocusing of research activity to better meet SSA's needs. Transfusion research hubs within and beyond SSA have been identified as a springboard network for expanding SSA transfusion research capacity.